Genetic Variability And Character Associations In Irrigated Rice (Oryza Sativa L) - Ghosal, S; Biswas, PL; Khatun, M; Khatun, S (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Eighteen advanced breeding lines were evaluated for yield and yield contributing characters to observe their variability, associations and direct and indirect effect on yield during Boro season, 2009. All the tested characters showed significant variation. Effective tillers/m2 and spikelet sterility (%) had high genotypic variance, high heritability, high genetic advance and high genotypic coefficient of variation. Effective tillers/m2, panicle length (cm), thousand grain weight (g) and growth duration (days) showed significant positive association with grain yield. Path coefficient analysis also revealed that effective tillers/m2, thousand grain weight (g) and growth duration (days) had higher direct effects on yield (t/ha). All together with the genetic variability, correlation and path analysis revealed that effective tillers/m2, thousand grain weight (g) and growth duration (days) are the most important yield components in rice. Therefore, from the present study it could be suggested that emphasize should be given on these characters for the selection of genotypes for higher grain yield in irrigated rice. Keywords: Rice (Oryza sativa L.); GCV; PCV; heritability; genetic advance; correlation DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9321 Bangladesh J. Pl. Breed. Genet., 23(2): 23-27, 2010